Primerjava dveh napitkov ob teku na dolge proge - Lainščak, Mitja (Medicinski razgledi, 1999)
Drinking adequate amounts of fluid of appropriate compositon during exercise can partly normalize abnormalities in homeostasis of body fluids and improve physical performance. The objective of this prospective comparative study was to test the effects of isotonic beverage (Izomaratonik, Krka) and water drunk during an 18 km run. Isotonic beverage supplements fluid lost during long distance running more adequately than water. Subjects ran 18 km in each of twoconsecutive trials. They drank 700 ml of water in the first trial and the same amount of isotonic beverage in the second. Before and after the run we measured their weight, blood pressure both in the sitting and supine position,and took the blood and urine samples. The study involved 11 men and one woman, all heallhy and well trained long-distance runners, with a mean ageof 34.9 +- 9.1 (SD) years, mean body height of 173.5+-7.2 (SD) cm and mean body mass of 73.0+- 9.8 (SD) kg. No differences were found between the two beverages concerning their effects on the performance and general feeling of the runners. The subjects, however, reported better tolerance for the isotonicbeverage; the difference being not significant. The decrease in the systolic blood presure, both in the supine and sitting position, was significantly greater during the water trial. The increase in serum concentrations of sodium and chloride was significantly lesser during the isotonic beverage trial. In conclusion, ingestion of the tested isotonic beverage stabilized blood pressure and minimized changes occurring in plasma and urine of the long-distance runners.
Keywords: Running; tek; športniki; Beverages; Isotonic solutions; pijače; Energy intake; telesne tekočine; fiziologija; Questionnaires; tekočine; Body weight; Blood pressure; Blood glucose; Potassium; Blood; Sodium; Chlorides; Urinalysis